Slab Cutter machine maintenance to improve the efficiency of Rubber products at PT Bridgestone - Sitinjak, Augustinus Foncianus; Siahaan, Azarya Nimrod Juwono (Journal of Engineering Science and Technology Management, 2026)
Industrial asset maintenance management is a determining factor in ensuring operational continuity and output quality in the rubber processing manufacturing sector. This report examines the effectiveness of Slab Cutter machine maintenance at PT Bridgestone Sumatra Rubber Estate (BSRE) based on observations conducted during an Industrial Internship (Practical Work Program). The background of this study is grounded in the critical role of the Slab Cutter machine as an initial processing unit that reduces the dimensions of raw rubber slabs into uniform pieces in order to optimize subsequent milling and drying processes. Disruptions to this machine often result in significant downtime and irregular rubber particle sizes, which ultimately reduce energy efficiency and daily productivity. The main objective of this observation is to evaluate the preventive maintenance procedures implemented, identify the root causes of mechanical failures, and analyze their impact on the consistency of crumb rubber quality. Through the application of a qualitative field observation method, it was found that synchronization between routine cleaning, bearing lubrication, and blade sharpening was able to reduce operational failures by more than 75%. The conclusion of this study emphasizes that a reliability-based preventive maintenance strategy not only extends the service life of the machine but is also a fundamental prerequisite for achieving sustainable production efficiency targets within the Bridgestone industrial environment. This report recommends the adoption of a data-based monitoring system to detect early component wear in order to minimize emergency repair costs.